Optimization Formulation of Semi-Finished Sponge Cake - Marinina E.; Sadygova M.; Kirillova T.; Kanevskaya I. (Техника и технология пищевых производств)
Introduction. The research improved the formulation of semi-finished sponge cake by using the method of generalized desirability function. Traditional components were substituted with new advantageous rye varieties of local selection. The main advantage of the rye variety «Memory to Bambyshev» is that rye flour obtained from the whole grain of this variety has a lower trypsin inhibitor (1.7 mg/g) compared to flour from such varieties as «Saratov 6» (2.16 mg/g). Thus, the digestibility of the grain of this variety is higher by 0.26%. The rye can be used in baking to produce dietary breads, low-calorie bakery products with bran, and animal feed. Study objects and methods. Cakes and pastries make 34.5% of the total volume of flour confectionery products. The study developed a new semi-finished sponge-cake product, which can serve as the basis for cakes and pastries. However, flour confectionery products are oversaturated with carbohydrates and fats, which increases their calorie content. A set of experiments was performed to study the effect of reducing the amount of sugar in the formulation and replacing wheat flour with rye flour on the quality of semi-finished sponge-cake product. A basic formulation for sponge cake was used as control sample. The test semples varied in content of sugar and flour made from various types of rye. The technological additives included Ovalet emulsifier (1.5% to flour) and Duo baking powder (0.1% to flour). Emulsifier «OVALET SUPER» (Bakels, Sweden) is a pasty substance that consists of emulsifying agents, water, and stabilizers and acts as an improver, stabilizer, and structurizer designed for the production of semi-finished sponge cakes, rolls, muffins, and cookies. Duo baking powder is a special highly effective tool that does not contain tartaric acid. It can be used for the production of various varieties of bread and confectionery, e.g. biscuits, rolls, gingerbread, etc. The obtained dough was easy to process. The new formulation increased the volume and color of the product, as well as slowed down the process of hardening. Results and discussion. The highest value of the generalized function of desirability belonged to the sample where white wheat flour was subsituted with 30% of rye flour and the sample with 100% of rye flour with a 40% sugar reduction. According to the specific desirability indicators, the mass fraction of moisture, the mass fraction of total sugar, energy value, and foaming ability of the semifinished product were higher than those of the control sample. Conclusion. The developed formulation and technology can expand the range of functional products.